Matching to sample as a justification for conceptual errors - Hernández-Castro, Rosendo (1997)
A brief analysis is carried out on the multiple uses that the methodology of matching to sample has in behavioral research. The relevance of the use of these tasks in the study of different types of psychological mechanisms in animals is discussed, acknowledging that it is unnecessaty to use, in behavioral research, many names to make reference to those mechanisms. A conceptual-historical analysis is proposed as a study tool to emphasize the risks of considering a type of methodology that can induce causal effects on behavior.